2017
DOI: 10.1128/aem.02490-16
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Germination Capacity and Germinant Receptor (Sub)clusters of Genome-Sequenced Bacillus cereus Environmental Isolates and Model Strains

Abstract: Spore germination of 17 Bacillus cereus food isolates and reference strains was evaluated using flow cytometry analysis in combination with fluorescent staining at a single-spore level. This approach allowed for rapid collection of germination data under more than 20 conditions, including heat activation of spores, germination in complex media (brain heart infusion [BHI] and tryptone soy broth [TSB]), and exposure to saturating concentrations of single amino acids and the combination of alanine and inosine. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Nevertheless, the majority of studies investigating B. cereus spore germination target spores present in foods, to either trigger germination in foodstuffs to eliminate germinated spores/vegetative cells or to completely avoid germination and outgrowth in foods [10,[277][278][279][280][281]. B. cereus spores can be triggered by nutrient-rich media, by amino acids such as alanine, cysteine, threonine or glutamine, by the purine ribonucleosides inosine and adenosine, by sugars, by heat treatment, or by their combination [279,[282][283][284][285]. Only a small number of publications focus on germination of B. cereus spores under (simulated) gastrointestinal conditions.…”
Section: Germination Of Sporesmentioning
confidence: 99%
“…Nevertheless, the majority of studies investigating B. cereus spore germination target spores present in foods, to either trigger germination in foodstuffs to eliminate germinated spores/vegetative cells or to completely avoid germination and outgrowth in foods [10,[277][278][279][280][281]. B. cereus spores can be triggered by nutrient-rich media, by amino acids such as alanine, cysteine, threonine or glutamine, by the purine ribonucleosides inosine and adenosine, by sugars, by heat treatment, or by their combination [279,[282][283][284][285]. Only a small number of publications focus on germination of B. cereus spores under (simulated) gastrointestinal conditions.…”
Section: Germination Of Sporesmentioning
confidence: 99%
“…There are three GRs: GerA responding to L-alanine, and GerB and GerK that collaborate in responding to L-asparagine, D-glucose, D-fructose and potassium chloride [10]. In contrast, there are seven functional GRs-GerR, GerK, GerG, GerL, GerQ, GerI and GerS-in B. cereus ATCC 14579 spores [22]. In particular, GerR, with the order GerRA-GerRC-GerRB, has a critical role in spore germination in response to L-alanine, or inosine alone and in food products, for example meat broth and rice water [23].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, heat activation has not been observed with C. difficile spores, which use an atypical GR to initiate germination (18,19). Additionally, responsiveness to heat activation in some strains of Bacillus may correlate with the genetic characteristics of GRs (20,21). Taken together, these findings suggest that the effect of heat activation on Bacillus species is probably mediated by a structural change in GR proteins or the inner spore membrane that makes GRs more accessible or receptive to nutrient-induced germination (11).…”
mentioning
confidence: 81%
“…Examination of the effect of sublethal heating on spore germination in a GerKC‐deficient isogenic mutant may therefore reveal additional mechanisms. Given that we have observed that responsiveness to heat treatment differs among several C. perfringens clinical isolates (our unpublished observation in 2017), better understanding of inter‐strain variations associated with different GerKC amino acid sequences would also assist in elucidating the mechanisms of heat activation .…”
mentioning
confidence: 94%
See 1 more Smart Citation